The formation of destination image of Khorezm region - Matniyozov Murodjon; Turaev Ogabek; Kalandarov Feruzbek; Egamberdiyev Oybek (BIO Web of Conferences, 2024)
This paper provides an analysis and conversation concerning the notion and assessment of destination image from a marketing perspective that encompasses various fields within the discipline. The main goal of the current study is to look at the structural relationships between destination image, tourist satisfaction, and destination loyalty, with a particular emphasis on the role that tourist satisfaction plays as an intermediary in the relationship between destination image and loyalty, particularly in the circumstances of cultural and historical tourism in the Khorezm region. The results show that the cognitive image directly influenced the affective image, affirming the process through which the destination image is formed. Furthermore, both cognitive and affective images had favorable impacts on satisfaction, which, in turn, emerged as a predictor of tourist loyalty. Moreover, Khiva’s reputation as a tourist destination in Uzbekistan is mostly based on the city’s extensive cultural history and allusions to prehistoric local practices.